(untitled) (Research, Society and Development, 2024)
Cachaça, the most consumed distilled beverage in Brazil, has shown an increase in consumption, making the professionalization of the sector necessary with new technologies and quality standardization. Although not mandatory, aging cachaça in wooden containers, such as barrels or casks, enhances the sensory characteristics of the beverage, as phenolic compounds are extracted from the wood and react with the alcohol. One of the techniques used in the maturation of cachaça is the creation of blends, which are mixtures of cachaças aged in different woods or in the same wood for different maturation times, aiming for balance and identity. Blends can elevate the qualities of cachaça, increasing its sensory complexity. The objective of the study was to evaluate the physicochemical profile of blends of cachaças aged in barrels made of different woods. The analyzed samples were cachaças produced in copper stills, originating from the states of São Paulo and Paraíba, collected directly from the bottling line. In the physicochemical analyses and the chemical aging markers of the blends, chemical and physical differences were observed, with a higher presence of syringaldehyde, vanillin, and coumarin. These chemical differences confirm the contribution of aging markers in the elaboration of cachaça blends.